Formation of nanostructured lipid carrier systems loaded with palm phytonutrients for application in cosmetics - Low, Chew Hung (2013)
Nanostructured lipid carrier has gained increasing interest in cosmetic field but the major problems are physical stability of NLC, chemical stability of bioactives in NLC and efficacy of NLC. The aim of this study was to develop nanostructured lipid carrier for delivery of antioxidant, palm phytonutrients (PP). The study was divided into four parts consisting of characterization of PP, development of preparation methods of NLC, optimization of formulation of NLC, and efficacy of NLC as delivery system for PP. Safety tests (in-vitro dermal and ocular irritation assay, human patch test and human repeated patch test) showed that PP was safe to be used as cosmetic bioactives. PP showed much higher fibroblasts cell viability compared to commercial phytonutrient (Tocomin 50% and Gold Tri. E) which indicated that PP was more effective in promoting proliferation of fibroblasts cells. Tocols and beta-carotene were found as the most abundant components in PP. Di(phenyl)-(2,4,6-trinitrophenyl)iminoazanium (DPPH), 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) nitric oxide radical scavenging assays analysis showed that PP had good scavenging activity. PP was found to have excellent UV-blocking activity as it absorbed light at UVA and UVB light region (290-400 nm). Particle size analysis, zeta potential analysis, rheological measurement and accelerated stability testing were used to assess the physical stability of NLC formulation. Two novel preparation methods of NLC which produced NLC with high physical stability and enhanced chemical stability of PP were successfully developed. The optimized NLC production conditions were 500-1000 bars homogenization pressure, 3 cycles of high pressure homogenization, and the cooling temperature was 25 ºC after hot high pressure homogenization. The optimized NLC formulation were 6% of Span 40 and Tween 80 (50:50) as surfactants, 20% of lipid phase containing mixture of hydrogenated palm kernel and palm glycerides and isopropyl palmitate (90:10) as emollients and 0.10% of PP as bioactives, and 0.5% of MC-NP4 as preservatives. The optimized formulation exhibited good physical and microbiological stability and enhanced chemical stability of PP in the formulation. NLC loaded with PP showed high physical stability and chemical stability of PP when compared to macroemulsion loaded with PP and nanoemulsion loaded with PP. Percentage of fibroblasts cells viability of NLC was much higher at concentration of 400-2000 μg/ml when compared to macroemulsion loaded with PP and nanoemulsion loaded with PP. Increase in percentage of fibroblasts cell viability indicated that more collagen could be produced to reduce skin aging. NLC loaded with PP greatly increased skin hydration and reduced skin roughness when compared to macroemulsion loaded with PP and nanoemulsion loaded with PP. This work concluded that NLC loaded with PP which exhibited good physical stability and chemical stability of PP, and promising anti-wrinkle efficacy was successfully developed.